18F-choline PET/CT for parathyroid scintigraphy: significantly lower radiation exposure of patients in comparison to conventional nuclear medicine imaging approaches. (15th February 2018) - Rep, Sebastijan; Hocevar, Marko; Vaupotic, Janja; Zdesar, Urban; Zaletel, Katja; Lezaic, Luka
Abstract: Background. Parathyroid subtraction scintigraphy (PSS) is the most commonly used imaging method for localisation of hyperfunctioning parathyroid glands (HPGs) in primary hyperparathyroidism (PHP), a common endocrine disorder. Hybrid (SPECT/CT) imaging with 99m Tc-sestaMIBI (MIBI) at an early and delayed phase (dual-phase imaging) may be the most accurate conventional imaging approach, but includes additional radiation exposure due to added CT imaging. Recently, 18 F-choline (FCH) PET/CT was introduced for HPG imaging, which can also be performed using the dual-phase approach. To date, no studies have compared organ doses and the effective dose (ED) from conventional subtraction scintigraphy, dual-phase MIBI SPECT/CT, and FCH PET/CT in the localisation of HPGs. Aim. In addition to the comparison of the diagnostic performance of FCH PET/CT and conventional scintigraphic imaging methods, the aim of the study was to measure the organ doses and the ED for conventional subtraction parathyroid imaging protocols, using dual-phase MIBI SPECT/CT as a potential conventional imaging method of choice and FCH dual-phase PET/CT as a potential future imaging method of choice for the localisation of HPGs. Materials, methods. Thirty-six patients referred for parathyroid imaging with a clinical indication of PHP underwent preoperative PSS and dual-phase SPECT/CT imaging with the addition of FCH PET/CT. The diagnostic performance of the imaging modalities was assessed by using histology results as a gold standard. Radiation exposure was calculated for the administered activities of radiopharmaceuticals using ICRP80 weighting factors and for CT exposure at hybrid imaging using dose-length products and the ImPACT CT Patient Dosimetry Calculator. Results . The diagnostic performance of FCH PET/CT was significantly better than that of conventional imaging modalities (sensitivity of 97% vs 64% and 46% for MIBI SPECT/CT and PSS, respectively, with comparable specificity of over 95% for all modalities). The highest radiation exposure was caused by conventional PSS (7.4 mSv), followed by dual-phase MIBI SPECT/CT (6.8 mSv). The radiation exposure was the lowest for dual-phase FCH PET/CT imaging (2.8 mSv). The added CT imaging for both hybrid approaches did not cause significant additional radiation exposure (1.4 mSv for MIBI SPECT/CT, additional 26.4% to overall exposure; 0.8 mSv for FCH PET/CT, additional 42.4% to overall exposure). Conclusion. In comparison to conventional scintigraphic imaging of HPGs, emerging hybrid (SPECT/CT, PET/CT) imaging techniques combine superior diagnostic performance with lower radiation exposure to patients.